Formic acid production through electrochemical reduction of CO2: A life cycle assessment - Aliya Banu (17017731) (2023)
CO2 electrochemical reduction can provide a sustainable pathway for fuel production. In this study, a life cycle assessment is performed on the electrochemical reduction process of CO2 to produce 1 kg of formic acid using experimentally obtained inventory data. A lab-scale conventional H-type electrochemical cell, consisting of Nafion 117 membrane and Sodium bicarbonate electrolyte, was used for the study. The working electrode consisted of a Lead-based electrocatalyst deposited on acid-treated tin foil. The life cycle assessment boundaries are defined, and the data is entered into the software. The environmental impacts are found to be 3.27 kg CO2 eq, 4.28 x10-3 kg SO2 eq, 2.12 x10-2 kg P eq, 3.85 × 10-11 kg CFC-11 eq and 8.35 m3 for climate change, terrestrial acidification, freshwater eutrophication, ozone depletion and water depletion for 1 kg formic acid produced, respectively. Overall, the required electricity for the operation of the electrochemical cell has the highest impact on climate change category accounting for 96% of the overall impact. The membrane and electrodes in the cell have a very low impact on the categories studied except ozone depletion. The membrane production accounts for 88% of the impact on ozone depletion. A sensitivity analysis is conducted on the lifetime of the electrodes, electricity source and water type. The findings from this study can help researchers, policymakers, and industrial stakeholders make critical decisions regarding material selection and optimization to increase the sustainability of the electrochemical reduction process for formic acid synthesis. Other Information Published in: Energy Conversion and Management: X License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecmx.2023.100441